Cainocreadium flesi sp. n. (Trematoda, Opecoelidae) — new trematode species from the Black Sea fishes - Korniychuk, J.; Gaevskaya, A.V (Vestnik zoologii, 2000)
Cainocreadium flesi sp. n. from the gut of the Black Sea flounder, Platichthys flesus luscus (Pallas), is described. It differs from C. labracis by the ovary shape, relative sizes of the cirrus-sac, ventral sucker and seminal vesicle and the egg size. It is shown that the trematodes described by S. U. Osmanov from the Black Sea flounders as C. labracis actually are C. flesi.